The dynamics of two harmful phytoplankton and herbivorous zooplankton system - Naji, Raid; Aaid, Asraa (Iraqi Journal of Science, 2023)
In this paper, a mathematical model consisting of the two harmfulphytoplankton interacting with a herbivorous zooplankton is proposed and studied.The existence of all possible equilibrium points is carried out. The dynamicalbehaviors of the model system around biologically feasible equilibrium points arestudied. Suitable Lyapunov functions are used to construct the basins of attractionsof those points. Conditions for which the proposed model persists are established.The occurrence of local bifurcation and a Hopf bifurcation are investigated. Finally,to confirm our obtained analytical results and specify the vital parameters, numericalsimulations are used for a hypothetical set of parameter values.